2023
DOI: 10.1093/rheumatology/kead019
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationships of tea and coffee consumption with gout: a prospective cohort study in the UK Biobank

Abstract: Objectives The association of tea or coffee consumption with gout is inconsistently reported. Few prospective studies have explored their dose-response relationship. Therefore, we aimed to quantitatively investigate the association between tea, coffee and the risk of developing gout. Methods The study included 447 658 participants in the UK Biobank who were initially free of gout. Tea and coffee consumption were assessed at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…A Meta-analysis showed that coffee had a significant reduction in serum uric acid and that moderate coffee intake may be advocated for primary prevention of gout [ 58 ]. Some prospective data suggest that long-term coffee consumption is associated with a lower risk of gout [ 59 , 60 ] and that coffee consumption has a strong nonlinear association in reducing the risk of gout [ 61 ]. In addition, one study found that coffee consumption was associated with lower serum uric acid levels and frequency of hyperuricemia, and the negative association with coffee seems to be through coffee components other than caffeine [ 60 ].…”
Section: Common Risk Factors For Gout and Dedmentioning
confidence: 99%
“…A Meta-analysis showed that coffee had a significant reduction in serum uric acid and that moderate coffee intake may be advocated for primary prevention of gout [ 58 ]. Some prospective data suggest that long-term coffee consumption is associated with a lower risk of gout [ 59 , 60 ] and that coffee consumption has a strong nonlinear association in reducing the risk of gout [ 61 ]. In addition, one study found that coffee consumption was associated with lower serum uric acid levels and frequency of hyperuricemia, and the negative association with coffee seems to be through coffee components other than caffeine [ 60 ].…”
Section: Common Risk Factors For Gout and Dedmentioning
confidence: 99%
“…In a prospective cohort study of 447,658 individuals, Guo H et al. ( 60 ) found that drinking more than 6 cups of tea per day decreased the risk of gout by 23%, suggesting a clear link between tea and gout reduction. Intriguingly, the effect of tea in reducing the risk of gout in our study occurred only in gout due to impairment of renal function and not in all types of gout, which may be because the renoprotective effect of tea was more pronounced in patients with pre-existing renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Esta normalização da reatividade inflamatória está provavelmente subjacente à capacidade do consumo regular de café diminuir a incidência de gota (Choi et al, 2007;H. Guo et al, 2023;, apesar de um impacto inconsistente nos níveis plasmáticos de ácido úrico (H. Guo et al, 2023;Jung et al, 2020), assim como um melhor controle da asma (Lin et al, 2022;Welsh et al, 2010) e de outras patologias respiratórias (Alfaro et al, 2018).…”
Section: Café E Saúde (Figura 2)unclassified
“…Esta normalização da reatividade inflamatória está provavelmente subjacente à capacidade do consumo regular de café diminuir a incidência de gota (Choi et al, 2007;H. Guo et al, 2023;, apesar de um impacto inconsistente nos níveis plasmáticos de ácido úrico (H. Guo et al, 2023;Jung et al, 2020), assim como um melhor controle da asma (Lin et al, 2022;Welsh et al, 2010) e de outras patologias respiratórias (Alfaro et al, 2018). O impacto do café, e da cafeína, no controle da autoimunidade (Iris et al, 2018;Sharif et al, 2017), é provavelmente associado ao papel chave de um dos principais alvos da cafeína, os receptores A2A da adenosina (Fredholm et al, 1999), como sistema STOP da reatividade imune-inflamatória (Ohta et al, 2006;Ohta & Sitkovsky, 2011).…”
Section: Café E Saúde (Figura 2)unclassified